Genetic variability of yam (Dioscorea trifida) genotypes in the Ucayali region, Peru - Tuisima Coral, Lady Laura (2022)
The aim of this research was to assess genetic variability of yam Dioscorea trifida genotypes using morphological descriptors for the germplasm collection conserved in the Agricultural Experiment Station in Ucayali, Peru. Thirty-eight morphological traits were evaluated for 30 D. trifida genotypes over ten years; from the data we estimated the Shannon-Weaver diversity index (H’) and the coefficient of variation and performed principal component analysis and cluster analysis. Qualitative traits with high phenotypic diversity index were: petiole anthocyanin (0.86), internal tuber color (0.86), petiole color (0.81) and stem color (0.80). The quantitative traits with the highest coefficient of variation were: tuber weight per plant (33.01) and tuber yield (32.99). Seventy-six percent of the morphological variability is explained by four principal components, the first component is constituted by the characters tuber width, tuber weight per plant, and tuber yield (29%). Five groups of genotypes were also identified with statistically significant differences, where group B stands out for its higher yield in fewer days to harvest. This research reveals wide morphological diversity in genotypes of D. trifida; these results can be used to strengthen the conservation, management, and genetic improvement initiatives of this important species in the Peruvian Amazon.